Effect of Fermentation of Aspergillus cristatus on Physicochemical Indexes and Flavors of Summer and Autumn Tea - Zhichao YANG; Xuandong ZHENG; Tianze SUN; Hui ZHANG; Shanshan XU; Dongdong MU; Xingjiang LI (Shipin gongye ke-ji)
In order to investigate the effect of Aspergillus cristatus in Golden Flower Fungus on the quality of fermented summer and autumn tea, six strains of Aspergillus cristatus were isolated and identified from Poria cocos tea in Shaanxi, and the strains were inoculated into sterilized summer and autumn teas for solid-state fermentation to analyse the physicochemical indexes and flavor changes of fermented summer and autumn teas. The results showed that compared with unfermented summer and autumn tea (CK), the overall water leachate content and the ratio of sweet to bitter amino acid content of fermented tea were significantly increased (P<0.05). The flavonoid content, tea polyphenol content, caffeine content, and total catechin content were significantly decreased (P<0.05). And 25 new ester and hydrocarbon volatile compounds were added. The sensory results showed that the main aromas of the tea were transformed before and after fermentation, and the fermented tea was endowed with pleasant floral, fruity, and sweet aromas. Correlation analysis of flavor substances and sensory flavor profiles showed that floral, fruity, and sweet aromas were positively correlated with (+)-limonene, phenethyl phenylacetate and others. In conclusion, significant differences (P<0.05) were found in the quality of summer and autumn teas fermented by different Aspergillus cristatus. And the quality of summer and autumn tea after fermentation by Aspergillus cristatus was better than that of CK. It was determined through the rank sum ratio comprehensive evaluation method that Aspergillus cristatus F improved the quality of summer-autumn tea relatively better.